Multicolor mechanoluminescent film based on fluorescent powder as well as preparation method and application of multicolor mechanoluminescent film

Preparation of BI3+and MN2+commonly doped ZNS/CAZNOS heterogeneous luminous materials through high temperature and solid -phase synthesis method, and compounds with polyvinyl alcohol to solve the problem of unstable luminous performance of mechanical luminous materials and difficulty in color adjustment. The control of the color and the stability of performance have extensive application potential.

CN119331602AActive Publication Date: 2025-01-21CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411447138.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In actual applications, mechanical luminescent materials have problems such as unstable luminous performance, difficulty in color adjustment, and material safety, which limits their wide application in the fields of visual sensing, information storage and pressure sensing.

Method used

A Bi3+ and Mn2+ co-doped ZnS/CaZnOS heterojunction mechanoluminescent material was prepared through a high-temperature solid-state synthesis method, and compounded with polyvinyl alcohol to prepare a flexible transparent film, achieving luminous colors ranging from cyan to white to orange-red. Controllable adjustment.

Benefits of technology

It achieves hue controllability and performance stability of mechanoluminescent materials, and has potential applications in fields such as temperature sensing, anti-counterfeiting and electronic signatures. The raw materials used are environmentally friendly, cheap and easy to obtain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331602A_ABST
    Figure CN119331602A_ABST
Patent Text Reader

Abstract

The invention discloses a multicolor mechanoluminescent film based on fluorescent powder and a preparation method and application thereof, and the preparation method comprises the following steps: preparing a series of mechanoluminescent materials with adjustable light colors through a high temperature solid phase method, and compounding the prepared mechanoluminescent materials with polyvinyl alcohol to prepare a flexible transparent film. The color change of cyan-yellow-orange red can be clearly observed by writing numbers' 1 ',' 2 'and' 3 'on the transparent film, which shows that the prepared mechanical luminescent material has great potential in the application fields of electronic signatures, anti-counterfeiting and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mechanoluminescent materials, and in particular relates to a multi-color mechanoluminescent film based on fluorescent powder and a preparation method and application thereof. Background Art

[0002] Light is the basis for the survival and development of any organism. It is also an important medium for communication with nature and a carrier for promoting information dissemination. With the continuous development and progress of human society and science and technology, people have a more thorough understanding of light. At the same time, the development and demand of various emerging applications have further stimulated people's enthusiasm for finding new luminescent materials. Luminescence is a special phenomenon, which is a result of the interaction between external influences and matter. According to different excitation methods, the luminescence phenomenon can be divided into photoluminescence, electroluminescence, mechanical luminescence, chemiluminescence, bioluminescence, thermoluminescence, etc. Compared with other luminescence phenomena, mechanical luminescence is a special luminescence phenomenon. Although the mechanical luminescence phenomenon has been recorded for a long time, the research on the mechanism of mechanical luminescence is still imperfect, which hinders the further development and practical application of mechanical luminescent materials. Therefore, it is particularly important to study mechanical luminescent materials with excellent luminescence properties and further explore their internal mechanisms.

[0003] Mechanoluminescence refers to the process of converting mechanical energy into light energy, which allows materials to emit light under different mechanical stimuli, such as compression, stretching, friction, and impact. Compared with photoluminescent and electroluminescent materials, mechanoluminescent materials can emit light directly under appropriate external mechanical stimuli without relying on light or electrical excitation. Due to this unique property, mechanoluminescent materials have great application potential in visual sensing, information storage, visual expression, pressure sensors, and organic piezoelectric display devices. Specifically, they can be used for real-time and multidimensional stress mechanical sensing. In the past 20 years, researchers have focused on developing mechanoluminescent materials with a variety of properties, including high mechanical sensitivity, high brightness, wide emission wavelength, excellent luminescence repeatability, and remarkable stability.

[0004] With the development of the field of mechanoluminescence, the exploration of new mechanoluminescent materials (including matrix materials and doping ions) has become the main breakthrough in this research direction. CaZnOS semiconductor materials have gradually become a hot topic of research due to their excellent piezoelectric and luminescent properties and simple preparation process. In addition, benefiting from the rapid development of heterojunction engineering, semiconductor heterojunctions have a strong positive effect on carrier transport at the interface and can regulate luminescence behavior.

[0005] Therefore, the present invention provides a multi-color force-induced luminescent film based on phosphors and a preparation method and application thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-color phosphor-based mechanoluminescent film and its preparation method and application, and a series of Bi 3+ and Mn 2+ Co-doped ZnS / CaZnOS heterojunction mechanoluminescent materials are prepared by changing the Mn 2+ The doping ratio of 200 μm / s has realized the controllable adjustment of the luminescent color from cyan-white-orange-red. The mechanical luminescent material is further compounded with polyvinyl alcohol to prepare a flexible transparent film, and the mechanical luminescent properties of the material are explored. The raw materials used in the present invention are harmless to the environment, cheap and easy to obtain. By combining mechanical force and luminescence, the conversion from mechanical energy to light energy is realized, and it is expected to be applied to many new applications.

[0007] A first aspect of the present invention provides a multi-color mechanoluminescent phosphor.

[0008] Specifically, a multi-color mechanoluminescent phosphor is composed of ZnS / Ca 0.96 ZnOS: 2% Bi, x% Mn (x=0, 0.05, 0.1, 0.2, 0.4, 0.7, 1, 2, 4, 8), 2% Li.

[0009] The second aspect of the present invention provides a multi-color force-induced luminescent film based on phosphors, and a preparation method and application thereof.

[0010] Specifically, the present invention proposes the following technical solution: a multi-color force-induced luminescent film based on phosphors and a preparation method and application thereof, comprising the following steps: (1) The required raw materials (CaCO3, ZnS, MnCO3, Bi2O3, Li2CO3) were weighed according to the calculated molar percentages and added to the agate mortar in sequence. (2) Add an appropriate amount of ethanol to the sample weighed in step (1), grind in an agate mortar until the ethanol is completely evaporated, and dry in a vacuum drying oven. (3) The powder obtained in step (2) was transferred into a crucible, and the crucible was placed in a tube furnace, and calcined at high temperature with argon as a protective gas to obtain a heterojunction mechanical luminescent material (ZnS / CaZnOS:Bi 3+ ,Mn 2+ ). (4) The mechanoluminescent material obtained in step (3) is used to prepare a polyvinyl alcohol (PVA) film that can generate light by friction. First, a polyvinyl alcohol solution with a concentration of 10% is prepared, and then a certain amount of the mechanoluminescent material is weighed and mixed with the polyvinyl alcohol solution. After the two are fully mixed using an ultrasonic cell crusher, the prepared solution is poured into a watch glass and dried in an oven to obtain a polyvinyl alcohol mechanoluminescent film.

[0011] Preferably, the ZnS / Ca prepared in step (1) 0.96 ZnOS: 2% Bi, x% Mn (x=0, 0.05, 0.1, 0.2, 0.4, 0.7, 1, 2, 4, 8), 2% Li using Bi 3+ and Mn 2+ By changing the Mn 2+ Concentration can be used to obtain fluorescent materials with better effects.

[0012] Preferably, in step (2), the grinding time in the agate mortar is 15-30 min, and the drying condition is drying in a vacuum drying oven at 60° C. for 30 min.

[0013] Preferably, the high temperature calcination process in step (3) is to heat from room temperature (25°C) to 800°C and keep it warm for 1 hour, then heat from 800°C to 1100°C and keep it warm for 4 hours, end the process and cool naturally to room temperature.

[0014] Preferably, the polyvinyl alcohol used in step (4) is type 1788, and the mass ratio of polyvinyl alcohol to deionized water in the polyvinyl alcohol solution obtained in step (4) is 1:10. The polyvinyl alcohol is slowly added into deionized water at 90° C., and the concentration of the prepared polyvinyl alcohol solution is 10%.

[0015] Preferably, the oven condition in step (4) is to dry at 60° C. for 8-10 hours to finally obtain the polyvinyl alcohol mechanoluminescent film.

[0016] The present invention also provides a multi-color force-induced luminescent film based on phosphor as described above, and a preparation method and application thereof.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The CIE chromaticity diagram shows that as Mn 2+ As the doping amount of is continuously increased, the luminescent color can be controllably adjusted from cyan-white to orange-red. Then the thermal stability of the obtained luminescent material is monitored, and the color gradually changes from cyan-white to orange-red as the temperature rises, proving that it has potential application value in the fields of temperature sensing and anti-counterfeiting. 2. The prepared mechanical luminescent material is compounded with polyvinyl alcohol to make a flexible transparent film. By writing the numbers "1", "2" and "3" on the transparent film, the color change from cyan to yellow to orange-red can be clearly observed, which shows that the prepared mechanical luminescent material has great potential in application fields such as electronic signature and anti-counterfeiting. 3. The raw materials used in the present invention are harmless to the environment, cheap and easy to obtain. By combining mechanical force and luminescence, the conversion from mechanical energy to light energy is achieved, and it is expected to be applied to many new applications.

[0016] The above content is an overview of the technical solution. The present invention will be further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to clearly illustrate the technical solutions for implementing the present invention, the implementation process and the drawings required for use in the embodiments are briefly introduced below. The following drawings only show some embodiments of the present invention and therefore should not be regarded as limiting the present invention in any form. Figure 1 For preparing different Mn in Examples 1-10 2+ Doping concentration of ZnS / CaZnOS: 2%Bi 3+ ,x%Mn 2+ The emission spectrum of . Figure 2 For preparing different Mn in Examples 1-10 2+ Doping concentration of ZnS / CaZnOS: 2%Bi 3+ ,x%Mn 2+ CIE chromaticity diagram. Figure 3 Mn in Example 11 2+ Pictures of handwriting on transparent PVA films prepared from samples with concentrations of 0%, 0.2%, and 2%, with "1", "2", and "3" written in sequence. DETAILED DESCRIPTION The technical solution of the present invention is further described below in conjunction with specific embodiments and drawings. However, the following embodiments are only intended to strengthen the description of the technical solution of the present invention and should not be interpreted as any limitation on the scope of the invention claimed. Example 1 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4361gZnS and 0.00739gLiCO3 without MnCO3, add them to an agate mortar in sequence, add an appropriate amount of ethanol, grind them in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry them in a vacuum drying oven at 60°C for 30min. Transfer the resulting powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as the protective gas. The specific heating program includes heating from room temperature (25°C) to 800°C and keeping warm for 1 hour, then heating from 800°C to 1100°C and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that in Mn 2+As the doping concentration of Mn increases from 0% to 8%, a cyan emission peak at 479nm and a red emission peak at around 590nm can be found. 2+ The doping concentration of Bi at 479nm is increasing. 3+ The intensity of the emission peak decreases continuously, and the Mn 2+ The intensity of the emission peak first increases and then decreases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that without Mn doping 2+ When , its CIE coordinates are (0.1615, 0.2379). Example 2 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4349gZnS, 0.00739gLiCO3 and 0.00144gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 0.05%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 0.05%, its CIE coordinates are (0.1754, 0.2495). Example 3 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4337gZnS, 0.00739gLiCO3 and 0.00287gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 0.1%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 0.1%, its CIE coordinates are (0.2026, 0.2730). Example 4 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4312gZnS, 0.00739gLiCO3 and 0.00575gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+When the concentration is 0.2%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 0.2%, its CIE coordinates are (0.2410, 0.2948). Example 5 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4264gZnS, 0.00739gLiCO3 and 0.0115gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 0.4%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 0.4%, its CIE coordinates are (0.3269, 0.3441). Example 6 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4190gZnS, 0.00739gLiCO3 and 0.02gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 0.7%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 0.7%, its CIE coordinates are (0.4671, 0.4106). Example 7 Weigh 0.0466gBi2O3, 0.96gCaCO3, 2.4118gZnS, 0.00739gLiCO3 and 0.0287gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+When the concentration is 1%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak increases. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 1%, its CIE coordinates are (0.5051, 0.4232). Example 8 Weigh 0.0575gBi2O3, 0.96gCaCO3, 2.3874gZnS, 0.00739gLiCO3 and 0.0287gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 2%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak reaches its maximum. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 2%, its CIE coordinates are (0.5447, 0.4391). Example 9 Weigh 0.115gBi2O3, 0.96gCaCO3, 2.339gZnS, 0.00739gLiCO3 and 0.0287gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+ When the concentration is 4%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak begins to decrease. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 4%, its CIE coordinates are (0.5550, 0.4160). Example 10 Weigh 0.23gBi2O3, 0.96gCaCO3, 2.241gZnS, 0.00739gLiCO3 and 0.0287gMnCO3, add them to an agate mortar in turn, add an appropriate amount of ethanol, grind in the agate mortar for 15-30min until the ethanol is completely volatilized, and dry in a vacuum drying oven at 60℃ for 30min. Transfer the obtained powder to a crucible, and put the crucible into a tubular furnace, and calcine at high temperature with argon as protective gas. The specific heating program includes heating from room temperature (25℃) to 800℃ and keeping warm for 1 hour, then heating from 800℃ to 1100℃ and keeping warm for 4 hours, end the program and cool naturally to room temperature, and grind the sintered product into powder for later testing and characterization. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The emission spectrum of Figure 2 As shown. Figure 2 It can be seen that when Mn is added 2+When the concentration is 8%, the Bi at 479nm 3+ The intensity of the emission peak decreases, and the Mn 2+ The intensity of the emission peak continues to decrease. Prepared samples ZnS / CaZnOS:Bi 3+ , Mn 2+ The CIE chromaticity diagram is as follows Figure 3 As shown. Figure 3 It can be seen that when doped with Mn 2+ When the concentration is 8%, its CIE coordinates are (0.5407, 0.4247). Embodiment 11 In the three groups of Mn obtained in Examples 1, 4, and 8 2+ After three groups of samples with doping concentrations of 0%, 0.2%, and 2%, three groups of 20g polyvinyl alcohol 1788 were weighed and slowly added to 200g deionized water at 90°C to prepare a polyvinyl alcohol solution with a concentration of 10%. Then, the above three groups of mechanical luminescent materials were weighed, mixed with the polyvinyl alcohol solution, and after the two were fully mixed using an ultrasonic cell crusher, the prepared solution was poured into a watch glass and dried in an oven at 60°C for 8-10h to obtain three groups of polyvinyl alcohol mechanical luminescent films. By fixing a transparent polyvinyl alcohol film on a table with transparent tape, one person writes on the film while another person takes photos and videos to obtain a picture of the writing process. The words "1", "2", and "3" are written in sequence, and "123" can be clearly seen in the picture, as shown in the figure. Figure 1 As shown, with the increase of Mn 2+ The color gradually deepens as the doping concentration increases, which shows that the 2+ The color of mechanical luminescence can be regulated by adjusting the doping concentration. At the same time, the prepared polyvinyl alcohol film can record the signatures or handwriting habits of different users and conduct specific analysis based on the strength of the applied stress. Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A multi-color luminescent film based on phosphor and its preparation method and application, characterized in that: The specific steps are as follows: (1) Weigh the required raw materials according to the calculated molar percentage and add them into an agate mortar in sequence; (2) adding an appropriate amount of ethanol to the sample weighed in step (1), grinding in an agate mortar until the ethanol is completely evaporated, and drying in a vacuum drying oven; (3) The powder obtained in step (2) was transferred into a crucible, and the crucible was placed in a tube furnace, and calcined at high temperature with argon as a protective gas to obtain a heterojunction mechanical luminescent material (ZnS / CaZnOS:Bi 3+ ,Mn 2+ ).

2. The multi-color force-luminescent film based on phosphors and its preparation method and application according to claim 1, characterized in that: The method also includes a fourth step, using the mechanical luminescent material obtained in claim 1 (3) to prepare a polyvinyl alcohol (PVA) film that can generate light by friction, first preparing a polyvinyl alcohol solution with a concentration of 10%, then weighing a certain amount of the mechanical luminescent material, mixing it with the polyvinyl alcohol solution, and using an ultrasonic cell crusher to fully mix the two, then pouring the prepared solution into a watch glass, and drying it in an oven to obtain the polyvinyl alcohol mechanical luminescent film.

3. The multi-color force-luminescent film based on phosphors and its preparation method and application according to claim 1, characterized in that: The ZnS / Ca0.96ZnOS:2%Bi,x%Mn (x=0, 0.05, 0.1, 0.2, 0.4, 0.7, 1, 2, 4, 8), 2%Li phosphor prepared in step (1) is specifically composed of CaCO3, ZnS, MnCO3, Bi2O3, Li2CO 3。 4. The multi-color force-luminescent film based on phosphors and its preparation method and application according to claim 1, characterized in that: In step (2), the grinding time in the agate mortar is 15-30 minutes, and the drying condition is drying in a vacuum drying oven at 60° C. for 30 minutes.

5. The multi-color force-luminescent film based on phosphors and its preparation method and application according to claim 1, characterized in that: The high temperature calcination process in step (3) is to heat from room temperature (25°C) to 800°C and keep it warm for 1 hour, then heat from 800°C to 1100°C and keep it warm for 4 hours, end the process and cool naturally to room temperature.

6. The multi-color force-luminescent film based on phosphors and its preparation method and application according to claim 2, characterized in that: The polyvinyl alcohol used is type 1788. The mass ratio of polyvinyl alcohol to deionized water in the polyvinyl alcohol solution obtained in the step of claim 2 is 1:

10. Polyvinyl alcohol is slowly added into deionized water at 90°C to obtain a polyvinyl alcohol solution with a concentration of 10%. The oven condition is to dry at 60°C for 8-10h to finally obtain the polyvinyl alcohol mechanical luminescent film.

Citation Information

Patent Citations

  • Mechanochromic light-emitting material

    JP2012158678A

  • Method of preparing mechanoluminescent material and composite material containing it

    US20210009897A1

  • Composite-phase mechanoluminescent materials with adjustable color and intensity, and preparation method thereof

    WO2020186767A1